Factors Influencing Hiv Preventive Practices among Female Sex Workers in Takoradi - Habib, H.H. (University of Ghana, 2016)
BACKGROUND: Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome, (HIV-AIDS) is an incurable disease estimated to cause an annual worldwide mortality of above 1 million, most of which are in Sub Saharan Africa alone (WHO, 2014). Female Sex Workers are a higher risk Key Population where HI is concentrated. FSW HIV prevalence in Ghana is 11.1%, several times higher than the national prevalence of 1.3% (NACP, 2014). This study focused on FSW in Takoradi, a city which has recently encountered a large influx of moneyed migrants working in the petroleum sector due to oil finds off the western coast of Ghana. AIM: The aim of the study was to investigate factors influencing HIV preventive practices among Female Sex Workers in Takoradi. METHOD: The study was a cross sectional study involving 121 FSW from the Takoradi Metropolis. A standardised questionnaire was administered to FSW in different hotspots to collect socio-demographic, comprehensive HIV knowledge, condom use and other relevant data. Data collected were audited, coded, entered into STATA version 13 and subsequently cleaned. Frequencies were run for each variable to determine statistics. Bivariate analyses was conducted to investigate the relationships between variables at P<0.05 significance. RESULTS: A total of 121 FSWs participated in the study out of which 58.68 % were brothel based and 41.32% were street/pub/club based. Awareness of HIV, condom use and knowledge of modes of transmission were highly reported although comprehensive knowledge on HIV was relatively low (26.45%). Self-perceived risk was also low. Most FSW reported high condom usage and negotiation efficacy with their paying clients although out of those who had non-paying partners, majority reported no condom usage and negotiation efficacy. Although there was significant level of alcohol and drug consumption, they did not significantly affect preventive behaviour. CONCLUSION: Findings indicate that although there is knowledge about HIV, it is only superficial. Moreover, risky sexual practices exist between FSW and their non-paying partners which indicates a gap in preventive behaviour and a necessity for appropriate targeted interventions.
Thesis(MPH)-University of Ghana, 2016
Keywords: Hiv Preventive Practices; Female Sex Workers; Takoradi